Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3856/vol42-issue3-fulltext-5
|View full text |Cite
|
Sign up to set email alerts
|

Stomach contents of the Pacific sharpnose shark, Rhizoprionodon longurio (Carcharhiniformes, Carcharhinidae) in the southeastern Gulf of California

Abstract: ABSTRACT. The feeding habits of the sharpnose shark Rhizoprionodon longurio of the SE Gulf of California are described using the stomach contents of 250 specimens (135 males and 115 females) obtained weekly from December 2007 to March 2008 in the two main landing sites of the artisanal fishing fleet of Mazatlan. The mean total length (TL) was 77.7 ± 12.8 cm and the respective ranges for males and females were 60-120 cm and 52-120 cm. Size distribution showed two modal groups (juveniles: 52-80 cm, mode 72.5 cm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…Al comparar los resultados del presente estudio con otros llevados a cabo en el mismo género, la concentración de Cu encontrada en el músculo (0.39 ± 0.14 mg/kg peso húmedo) de R. terraenovae que es una especie ictiófaga con una dieta basada en teleósteos (Viana-Morayta et al, 2020), fue mayor a la concentración reportada por Adel et al (2017) para la especie R. longurio (0.23 mg/kg, peso húmedo) la cual se alimenta principalmente de cefalópodos (Osuna-Peralta et al, 2014), pero menor a la concentración de Cu presente en el músculo de R. acutus (1.10 mg/ kg, peso húmedo), cuya dieta está basada igualmente en teleósteos, pero con una gran proporción de organismos bentónicos (crustáceos, moluscos; Ba-A et al, 2013). Dichas diferencias de concentraciones reportadas pueden deberse a las diferentes porciones de Cu que ingiere cada especie de acuerdo a la dieta (tabla 4).…”
Section: Discussionunclassified
“…Al comparar los resultados del presente estudio con otros llevados a cabo en el mismo género, la concentración de Cu encontrada en el músculo (0.39 ± 0.14 mg/kg peso húmedo) de R. terraenovae que es una especie ictiófaga con una dieta basada en teleósteos (Viana-Morayta et al, 2020), fue mayor a la concentración reportada por Adel et al (2017) para la especie R. longurio (0.23 mg/kg, peso húmedo) la cual se alimenta principalmente de cefalópodos (Osuna-Peralta et al, 2014), pero menor a la concentración de Cu presente en el músculo de R. acutus (1.10 mg/ kg, peso húmedo), cuya dieta está basada igualmente en teleósteos, pero con una gran proporción de organismos bentónicos (crustáceos, moluscos; Ba-A et al, 2013). Dichas diferencias de concentraciones reportadas pueden deberse a las diferentes porciones de Cu que ingiere cada especie de acuerdo a la dieta (tabla 4).…”
Section: Discussionunclassified
“…Trophic levels that could not be identified up to a species level were obtained from Cortés (1999). The trophic overlap was calculated from a non-parametric analysis of similarities (ANOSIM) with software PRIMER-E 7 (Clarke and Gorley, 2006), where values from −1 to 1 were obtained (Osuna-Peralta et al ., 2014). Positive values mean similarity between sites, values close to zero do not show differences in sites, and negative values demonstrate a higher similarity (Osuna-Peralta et al ., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The trophic overlap was calculated from a non-parametric analysis of similarities (ANOSIM) with software PRIMER-E 7 (Clarke and Gorley, 2006), where values from −1 to 1 were obtained (Osuna-Peralta et al ., 2014). Positive values mean similarity between sites, values close to zero do not show differences in sites, and negative values demonstrate a higher similarity (Osuna-Peralta et al ., 2014). To complement ANOSIM, a similarity of percentages of prey species was realised (Clarke, 1993), which determines the level of significance of the results and the possible diet overlap between areas.…”
Section: Methodsmentioning
confidence: 99%
“…There is some evidence for ontogenetic shifts in diet in R. longurio (Alatorre-Ramirez et al, 2013;Trejo Ramírez, 2017), although this is not consistent between all studies (Osuna-Peralta et al, 2014) and to date no evidence has been found to support sex-based differences in trophic ecology (Alatorre-Ramirez et al, 2013). Given apparent seasonal and geographical variation in trophic ecology, long-term trophic studies will be required to determine the extent to which ontogenetic trophic niche shifts are present.…”
Section: Trophi C Ecologymentioning
confidence: 99%